ISOLATION AND CHARACTERISATION OF MICRO-ORGANISMS WITH INDUSTRIAL IMPORTANCE FROM SISAL BOLE ROTS - Mhaiki, Consolatha J. N; Masanja, Enock; Katima, Jamidu H. Y; Rajarao, Gunaratna K; Dalhammar, Gunnel (Tanzania Journal of Engineering and Technology, 2017)
Investigation of microorganisms naturally acclimatized to Agave hybrid H 11648 (sisal bole rot) was conducted, with the aim of isolating and characterizing Aspergillus niger strains for industrial use. Microorganism were identified morphologically and then confirmation made by polymerase chain reaction (PCR). Results showed the existence of four major groups, listed in order of abundances as follows; Aspergilli (36.0 ±0.8) %, Penicillin (28.0 ±0.1) %, Yeast (15.0 ±1.6) %and Fusarium (10.0 ±0.12) %. The main groups of Aspergilli strains were A. nidulans, A. tamari and A. niger in ratios (3:2:2), respectively. Several endo-spore forming non-enteric gram (-) rods and coccid bacteria identified by API 20 NE identification systemincluded,Brevundimonas diminuta sp, Shewanella putrefaciens sp, Brevundimonas vesicularis sp and Pasteurella sp. Results showed that sisal bole rot stems hosts a high bio-diversity of microorganism species other than A. niger. Exploitation of the individual strains is recommended. This could eventually produce strains for precursors of industrially and therapeutically metabolites.